Stable ≠ Sustainable: Delta Dynamics Versus the Human Need for Stability. Issue 7 (27th July 2021) - Passalacqua, P.; Giosan, L.; Goodbred, S.; Overeem, I.
Abstract: Arising from the non‐uniform dispersal of sediment and water that build deltaic landscapes, morphological change is a fundamental characteristic of river delta behavior. Thus, sustainable deltas require mobility of their channel networks and attendant shifts in landforms. Both behaviors can be misrepresented as degradation, particularly in context of the "stability" that is generally necessitated by human infrastructure and economies. Taking the Ganges‐Brahmaputra‐Meghna Delta as an example, contrary to public perception, this delta system appears to be sustainable at a system scale with high sediment delivery and long‐term net gain in land area. However, many areas of the delta exhibit local dynamics and instability at the scale at which households and communities experience environmental change. Such local landscape "instability" is often cited as evidence that the delta is in decline, whereas much of this change simply reflects the morphodynamics typical of an energetic fluvial‐delta system and do not provide an accurate reflection of overall system health. Here we argue that this disparity between unit‐scale sustainability and local morphodynamic change may be typical of deltaic systems with well‐developed distributary networks and strong spatial gradients in sediment supply and transport energy. Such non‐uniformity and the important connections between network sub‐units (i.e., fluvial, tidal, shelf) suggest that delta risk assessments must integrate local dynamics and sub‐unit connections with unit‐scale behaviors. Structure and dynamics of an integrated deltaic network control the dispersal of water, solids, and solutes to the delta sub‐environment and thus the local to unit‐scale sustainability of the system over time. Plain Language Summary: River deltas are fascinating complex systems that are densely populated and host valuable resources. Prone to rapid change in response to various forcing agents and human modifications, low‐lying deltas are facing environmental deterioration. Particularly in the last decade, while sea level rise accelerated, research on delta systems has increased considerably through observational studies, remote sensing, and numerical modeling. Many such studies attempt to address the question: "Will deltas be sustainable in the near future?" The narrow range of answers to this question are negatively skewed, but we argue here for a more precise perspective that acknowledges the scale dependency of the analysis and the location within the distributary network of a delta and recognizes that local instabilities caused by natural delta dynamics are not a sign of "deterioration" as they are often mischaracterized, but rather a requirement for sustaining a large delta needing sediment dispersed to a broad area. So, while delta dynamics present a challenge for humans and delta management, they are also a key piece to delta sustainability. Key Points: Sediment dispersal on delta plains is non‐uniform and controlled by the delta network structure Deltas can be sustainable at system scale but at the expense of human desire for stability in space and time Network dynamics (instabilities) are required for deltas' sustainability and need to be accounted for in adaptive delta management strategies